Historical-educational Research in Galicia, 2002-2014 - Costa Rico, Antón; Malheiro Gutiérrez, Xosé M. (Historia y Memoria de la Educación, 2016)
Using two previous reports as a reference, this paper examines the status of historical-educational research in Galicia and its contributions from the beginnings of the twenty-first century to the present. This particular contribution, rooted in the general studies and criteria of the sociology of knowledge, tests the reason for the historical-educational studies mentioned, their variability, their research problems, dominant themes and methodology, together with features characterizing the authors as well as different presentations of doctoral theses, monographs, book chapters and academic articles. In light of the aforementioned data, the authors of the test carry out an interpretive balance highlighting the critical aspects that limit this considerable regional historiography of education.